2020
DOI: 10.3390/ma13020375
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EGFR-Coated Gold Nanoparticles In Vitro Carry 5-Fluorouracil to Colorectal Cancer Cells

Abstract: The aim of the current study is to present a strategy to improve the efficiency of 5-fluorouracil (5-FU), which is widely used as antineoplastic agent against solid tumors-based on the use of gold nanocarriers to overcome the resistance of colorectal cancer cells. 5-FU was loaded on gold nanoparticles (AuNP) coated with anti-EGFR antibodies in order to target them towards colorectal cancer cells that overexpress epidermal growth factor receptors (EGFR). Physicochemical characterization has shown that AuNP size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…This in vitro study identified that anti-EGFR functionalisation increased the targeting potential of the AuNRs to EGFR expressing cell lines. Our findings in this study are supported by other studies including colorectal cancer [26], cervical cancer [27], skin cancer [28] and others where each of them found an increased uptake of functionalised gold nanoparticles in EGFR expressing cancer cells. In our study, although we used two cancer cell lines with an almost equal level of EGFR expression as shown by flow cytometry (Fig.…”
Section: Taunrs But Not Uaunrs Are Increasingly Associated With Egfr-supporting
confidence: 91%
See 1 more Smart Citation
“…This in vitro study identified that anti-EGFR functionalisation increased the targeting potential of the AuNRs to EGFR expressing cell lines. Our findings in this study are supported by other studies including colorectal cancer [26], cervical cancer [27], skin cancer [28] and others where each of them found an increased uptake of functionalised gold nanoparticles in EGFR expressing cancer cells. In our study, although we used two cancer cell lines with an almost equal level of EGFR expression as shown by flow cytometry (Fig.…”
Section: Taunrs But Not Uaunrs Are Increasingly Associated With Egfr-supporting
confidence: 91%
“…All four cancer cell lines were cultured in triplicate, on a 22 mm x 22 mm glass coverslips, as described previously. Biotinylated anti-EGFR monoclonal antibody was conjugated with AuNRs as described above [25] [24][25][26]. After culturing the cells for 24 hr on coverslips, the supernatants were removed and either tAuNRs or uAuNRs in 2 ml fresh complete medium were added into each well.…”
Section: Quantification Of Aunr Targetingmentioning
confidence: 99%
“…Its serious side effects, including severe gastrointestinal toxicity, hematologic disturbance, and heart toxicosis, limit its clinical benefits [ 38 ]. In this sense, a new strategy for improving 5-Fu efficiency was developed by Liszbinski and coworkers based on 5-Fu loading on gold nanoparticles coated with epidermal growth factor receptors antibodies (anti-EGFR) for colorectal cancer treatment [ 39 ]. Other recent approaches for improving the colon delivery of 5-fluoracyl include the preparation and optimization of 5-Fu-loaded biogenic gold nanoparticles with pluronic-based coatings [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies are also widely used for nanocarrier functionalization based on their inherent capability to specifically recognize their targets, and the promising results of cetuximab and panitumumab administration in improving clinical outcomes for mCRC patients lead to the use of these molecules as functionalization agents to direct nanoparticles towards tumor cells that overexpress EGFR. Several anti-EGFR-coated nanoparticles loaded with 5-FU were synthesized for CRC applications and showed superior colorectal cancer cell specificity and cytotoxicity of the novel drug-delivery systems [ 123 , 124 , 125 ]. An alternative for antibody use are aptamers, small single-stranded DNA or RNA molecules that present superior binding specificity and affinity for targeted molecules and low immunogenicity [ 126 ].…”
Section: Targeting Strategies For Drug-delivery Systems In Crcmentioning
confidence: 99%